Protein and starch content in winter wheat grain at different stages of growth and maturation - I. I. Sharapov; Yu. A. Sharapova; M. R. Abdryaev (Зерновое хозяйство России)
The current study was conducted in 2018, 2019 and 2021, on the experimental plots of the Volga Region RIBSP. The object of the study was the winter common wheat variety ‘Povolzhskaya Niva’. The purpose was to study the process of protein and starch accumulation in winter wheat grain at different stages of growth and maturation, under different weather conditions of the vegetation period. For this purpose, ears were selected at 6 stages of growth and maturation of winter wheat grain (according to the BBCN scale). The ears were dried to 14 % moisture. Protein and starch content was estimated by the InfraLum FT infrared analyzer. The weather conditions were contrasting, the HTC for the period of growth and maturation of winter wheat grain in 2018 and 2019 was characterized as dry (0.1 and 0.2, respectively), and 2021 as very dry (0.65). The lowest protein percentage in grain was identified in 2018 (11–13 %), the highest was in 2021 (13–15 %). Low protein percentage was established at the stage of late milk maturity (12 % on average for 3 years), and at the stage of early full maturity it was high (14 % on average for 3 years). Over the years of study, the starch content in winter wheat grain was high. Starch content in wheat grain at the stages of growth and maturation varied due to a greater extent on the weather conditions of the years of study. At the stages of middle and late milk maturity, there was a positive strong correlation between protein and starch content (0.859 and 0.951, respectively). Starting from the stage of early wax maturity and up to early full maturity, there was a negative correlation (from the mean statistical of 0.588 to the strong statistical of 0.987).